Efektifitas Senam Aerobik Low Impact Terhadap Perubahan Tekanan Darah Pada Lansia Dengan Hipertensi Di Posyandu Matahari Wilayah Kerja Puskesmas Muncang Kabupaten Lebak: Effectiveness of Low Impact Aerobic Exercise on Changes in Blood Pressure in Elderly People with Hypertension at Posyandu Matahari, Muncang Health Center Working Area, Lebak Regency - Fauziah, Iim (Indonesian Scholar Journal of Nursing and Midwifery Science, 2023)
Introduction: WHO data explains that 1,13 Billion people in the world had Hypertension in 2015. The results of a preliminary study in February 2022 found that 71,8% of a total of 128 elderly people had Hypertension. The number of elderly people with Hypertension at Matahari Integrated Healthcare Center increased in 2021 by 51,6%. There are still many elderly people with Hypertension who have an unhealthy lifestyle  Methods: This research uses descriptive quantitative research methods with the Secondary Data Analysis (ADS) approach. ADS is a method by utilizes secondary data as the main data source. Utilizing the secondary data in question is by using an appropriate statistical test technique.  Results: Based on the results of the frequency distribution it shows that there is a relationship between gender, age, education, occupation, and those who do low-impact aerobics with blood pressure. The results of the analysis of systolic blood pressure who did gymnastics ≥ 5 times experienced a decrease in blood pressure these results stated that the results of the Wilcoxon statistical test with a significance degree of α (0,05) obtained p-value = < 0,001 <0,005; there was a significant effect on gymnastics Low Impact Aerobics on changes in blood pressure before and after Low Impact Aerobics for the elderly at the Matahari Integrated Healthcare Center in the working area of the Muncang Health Center Lebak Regency. As for diastolic blood pressure a p-value < 0,001 was obtained there was a significant difference before and after being given Low Impact Aerobics to changes in blood pressure.  Discussion: there was a significant effect of gymnastics Low Impact Aerobics on changes in blood pressure before and after Low Impact Aerobics for the elderly at the Matahari Integrated Healthcare Center in the working area of the Muncang Health Center Lebak Regency. As for diastolic blood pressure, there was a significant difference before and after being given Low Impact Aerobics to changes in blood pressure.